2013
DOI: 10.1096/fj.13-234104
|View full text |Cite
|
Sign up to set email alerts
|

Losartan, an angiotensin II type 1 receptor blocker, protects human islets from glucotoxicity through the phospholipase C pathway

Abstract: As shown in a large clinical prospective trial, inhibition of the renin-angiotensin system (RAS) can delay the onset of type 2 diabetes in high-risk individuals. We evaluated the beneficial effects of RAS inhibition on β-cell function under glucotoxic conditions. Human islets from 13 donors were cultured in 5.5 mM (controls) or 16.7 mM glucose [high glucose (HG)] for 4 d with or without losartan (5 μM), a selective AT1R blocker, and/or U73122 (2 μM), a selective PLC inhibitor, during the last 2 d. HG induced R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…Thus, there may be a connection between AGTR1 activation and ER stress. This notion was supported by results from a recent study which indicated that high levels of glucose up-regulated the expression of AGTR1 and AGT mRNA in human islets, leading to the activation of islet RAAS (Madec et al 2013). AGTR1 was activated through phospholipase C and caused the depletion of ER calcium.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Thus, there may be a connection between AGTR1 activation and ER stress. This notion was supported by results from a recent study which indicated that high levels of glucose up-regulated the expression of AGTR1 and AGT mRNA in human islets, leading to the activation of islet RAAS (Madec et al 2013). AGTR1 was activated through phospholipase C and caused the depletion of ER calcium.…”
Section: Discussionmentioning
confidence: 60%
“…The reduction in ER calcium levels induced ER stress, which then induced b-cell dysfunction and apoptosis. Losartan showed a protective effect against glucotoxicity via inhibition of expression of AGTR1 and reduction of ER stress (Madec et al 2013). All of these lines of evidence indicated that testosterone and losartan inhibit similar aspects of high-glucose activated AGTR1.…”
Section: Discussionmentioning
confidence: 87%
“…Increased IP3R2 amounts may reflect important changes in Ca 2+ homeostasis and release of Ca 2+ from the ER. We have previously shown that exposure of human islets to high glucose concentrations led to increased levels of IP3R2 both at the mRNA and protein levels, as well as reduced levels of sarco-endoplasmic reticulum Ca 2+ ATPase 2b (SERCA 2b) pump [21]. Depletion of reticular Ca 2+ stores results in dysfunction of protein folding activation of the unfolded protein response (UPR), which leads to ER stress and may also alter mitochondria [22].…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] On the other hand, ARBs, the first line antihypertensive agents in T2DM patients, have recently been shown to exert beneficial effects on pancreatic β-cell function as well as on the insulin signaling cascades in skeletal muscle cells and hepatocytes. [16][17][18][19] It is therefore clinically relevant to determine whether the beneficial effects of DPP-4 inhibitor on pancreatic β-cell function could be observed in T2DM patients treated with ARBs. Our findings demonstrated for the first time that the DPP-4 inhibitor sitagliptin improved pancreatic β-cell function in ARB-treated T2DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 In addition, ARBs have recently been reported not only to improve insulin sensitivity, but also to preserve pancreatic β-cell function in both animal experiments and clinical studies. [16][17][18][19] Therefore, it is clinically relevant to investigate whether the beneficial effect of DDP-4 inhibitors could be exerted in ARB-treated T2DM patients.…”
Section: Introductionmentioning
confidence: 99%